Phenology of four tree species in an Atlantic Forest fragment in Southern Minas Gerais - Nathan Felipe Alves; Paulo Oswaldo Garcia (Revista Agrogeoambiental)
Periodic behaviors in plants are biological events that determine the successful development and reproduction of individuals of plant species and can be investigated through phenological studies. In this context, a phenological study of the tree species Croton floribundus Spreng., Cedrela fissilis Vell., Machaerium nyctitans (Vell) Brenth. and Machaerium villosum Vogel. was carried out by us in an Atlantic Forest fragment located in Federal Institute of Southern Minas Gerais - Campus Muzambinho, which is inserted in a region with well-defined double climatic seasonality, being individuals of the species monitored monthly between November 2020 and October 2021. The objective was to monitor the occurrence of vegetative and reproductive phenophases, which included growth and leaf fall, flowering and fruiting, which were observed with the aid of binoculars and then evaluate the correlation between these behaviors and the climatic variables of the study region. Correlations were obtained between climatic variables and vegetative and reproductive events expressed by the studied species. It was then observed that endogenous characteristics along with seasonal pressures influenced the time and period of phenophases, as well as the pollination and dispersal syndromes linked to these behaviors. The information in this work shows a way to understand the autoecology and population dynamics of these species, contributing to the conservation of biodiversity, as well as to the sustainable use of resources.